Swine influenza viruses and pandemic H1N1‐2009 infection in pigs, Myanmar. Issue 6 (14th June 2020) - Mon, Pont Pont; Thurain, Khin; Janetanakit, Taveesak; Nasamran, Chanakarn; Bunpapong, Napawan; Aye, Aung Myo; San, Yin Yin; Tun, Than Naing; Amonsin, Alongkorn
Abstract: Swine influenza virus (SIV) causes respiratory diseases in pigs and has impacts on both animal and human health. In this study, we conducted swine influenza surveillance in pig farms in the Yangon and Bago regions, Myanmar, during 2017–2019. Nasal swabs ( n = 500) were collected from pigs in 10 swine farms. Our results showed that 11 out of 100 pooled samples (11%) were positive for influenza A virus (IAV) by real‐time RT‐PCR. Five SIVs could be isolated and could be subtyped as SIV‐H1N1 ( n = 4) or SIV‐H3N2 ( n = 1). The viruses were further characterized by whole‐genome sequencing and classified as pdmH1N1‐2009 ( n = 3), reassortant H1N1 ( n = 1) or reassortant H3N2 ( n = 1). Phylogenetic analysis of Myanmar SIVs showed that all genes of the three SIV‐H1N1 (pdmH1N1‐2009) were clustered with viruses of the pdm/09 lineage. For one SIV‐H1N1 (rH1N1), the HA1 gene was clustered with those of endemic SIVs of the classical swine lineage, and seven genes were clustered with those of viruses of the pdm/09 lineage. For SIV‐H3N2 (rH3N2), the HA3 and NA2 genes were clustered with those of endemic SIVs of the human‐like swine lineage, while six internal genes were clustered with those of viruses of the pdm/09 lineage. Genetic analysis indicated that all the Myanmar SIVs possessed amino acids that favour binding to the human receptor. All the Myanmar SIVs contained amino acids related to amantadine resistance but not oseltamivir resistance. Notably, the pdmH1N1‐2009 virus might have been circulating in the Myanmar pig population for a period of time after pdmH1N1‐2009 outbreaks in humans. Then, reassortment between endemic SIV‐H1N1 or SIV‐H3N2 and pdmH1N1‐2009 in pig farms in Myanmar could have occurred. Our findings ascertained the genetic diversity of SIVs, especially pdmH1N1‐2009, in the pig population in Myanmar, with zoonotic and reverse zoonotic potentials.